2022
DOI: 10.1177/09603271211069982
|View full text |Cite
|
Sign up to set email alerts
|

The influence of PM2.5 exposure on kidney diseases

Abstract: The harm of air pollution to public health has become a research hotspot, especially atmospheric fine-particulate matter (PM2.5). In recent years, epidemiological investigations have confirmed that PM2.5 is closely related to chronic kidney disease and membranous nephropathy Basic research has demonstrated that PM2.5 has an impact on the normal function of the kidneys through accumulation in the kidney, endothelial dysfunction, abnormal renin-angiotensin system, and immune complex deposition. Moreover, the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 85 publications
0
15
0
Order By: Relevance
“…However, it is well known that acute and chronic exposure of heavy metals, major components of PM, leads to a variety of kidney injury including renal cell damage, tubular dysfunction, interstitial necrosis, and fibrosis of renal tissue ( BaSalamah et al., 2018 ; Lentini et al., 2017 ). In addition, accumulating evidence suggests that kidney could be a toxicological target for exposure to PM ( Bowe et al., 2017 ; Xu et al., 2022 ). More experimental and clinical studies on the possible impact of PM exposure on kidney disease are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is well known that acute and chronic exposure of heavy metals, major components of PM, leads to a variety of kidney injury including renal cell damage, tubular dysfunction, interstitial necrosis, and fibrosis of renal tissue ( BaSalamah et al., 2018 ; Lentini et al., 2017 ). In addition, accumulating evidence suggests that kidney could be a toxicological target for exposure to PM ( Bowe et al., 2017 ; Xu et al., 2022 ). More experimental and clinical studies on the possible impact of PM exposure on kidney disease are needed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple epidemiological results have reported that PM 2.5 exposure is related to kidney, blood lipid levels and cardiovascular disease. PM 2.5 was closely associated with kidney injury, especially chronic kidney disease (CKD), studies showed that PM 2.5 concentrations were positively associated with the risk of CKD, even harder in younger adults (< 65 years) and men than in elder populations (≥65 years) and women ( 3 ). In middle-aged women, long-term exposure to PM 2.5 can increase the prevalence of cardiac metabolic diseases, and the most relevant is hyperlipoproteinemia; PM 2.5 exposure is negatively correlated with the protective lipoprotein content in the body and positively correlated with the atherosclerotic lipoprotein content ( 10 , 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Global Burden of Disease Research Report ( 2 ), persistent and intense air pollution has become an immense burden on healthcare and health economy globally. By 2019, air pollution has been the fourth largest risk factor in the world ( 3 ). Particulate matter (PM), especially those with a diameter of 2.5 microns or less (also called fine particulate matters or PM 2.5 ), is a common proxy indicator for air pollution, which affects more people than any other pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of damage from PM 2.5 to the kidney involve inflammation, oxidative stress, apoptosis, DNA damage, and autophagy (Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…PM 2.5 can unbalance the kidney function by accumulation in the kidney tissue, endothelial dysfunction, abnormal renin-angiotensin system, and immune complex deposition. The mechanisms of damage from PM 2.5 to the kidney involve inflammation, oxidative stress, apoptosis, DNA damage, and autophagy (Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%